Influence of the activation mode of a self-etch resin-based luting cement upon the metabolism of odontoblast-like cells - De Mjendonça, Adriano Melo; De Oliveira, Camila Favero [UNESP]; Hebling, Josimeri; De Souza Costa, Carlos Alberto [UNESP] (My University, 2011)
Purpose: To evaluate the cytotoxicity of a self-etch resin-based luting cement, RelyXUnicem (RXU) upon chemical or dual cure and with or without interposition of IPS d.SIGN (IPSD) or IPS Empress II (IPSE) ceramic discs between cement and light source. Methods: 112 RXU specimens were subjected to different curing conditions and incubated in culture medium (DMEM) to obtain extracts. The following groups were formed: Gl: DMEM (control); G2: dual RXU; G3: chemical RXU; G4: dual RXU+IPSD; G5: chemical RXU+IPSD; G6: dual RXU+IPSE; and G7: chemical RXU+IPSE. Cultured odontoblast-like cells were incubated for 24 hours in contact with the extracts. Data from cell metabolism (CM), total protein dosage (TPD) and alkaline phosphatase activity (APA) were obtained and analyzed statistically (α= 0.05; Kruskal Wallis and Mann-Whitney tests). Cell morphology was analyzed by SEM. Results: CM and APA were significantly lower in G3 and G7 than in Gl (P< 0.05). Significant TPD decrease occurred in G5 and G7 compared to Gl (P< 0.05). Only G4 and G6 presented CM changes. RXU caused no cytotoxicity when subjected to dual cure without ceramic interposition. However, mild cytopathic effects were observed after chemical setting without ceramic interposition, and after chemical and dual activation under ceramic discs.